2010 18th International Packet Video Workshop 2010
DOI: 10.1109/pv.2010.5706838
|View full text |Cite
|
Sign up to set email alerts
|

Subjective quality assessment of error concealment strategies for 3DTV in the presence of asymmetric transmission errors

Abstract: International audienceThe transmission of 3DTV sequences over packet based networks may result in degradations of the video quality due to packet loss. In the conventional 2D case, several different strategies are known for extrapolating the missing information and thus concealing the error. In 3D however, the residual error after concealment of one view might leads to binocular rivalry with the correctly received second view. In this paper, three simple alternatives are presented: frame freezing, a reduced pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 5 publications
3
37
0
Order By: Relevance
“…Even so, some subjective tests have been already presented evaluating the performance of coding methods [14] and the effects of transmission errors [15], using methodologies based on those existing for traditional video, trying to take into account intrinsic factors related to the 3D visual experience, like visual discomfort.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, some subjective tests have been already presented evaluating the performance of coding methods [14] and the effects of transmission errors [15], using methodologies based on those existing for traditional video, trying to take into account intrinsic factors related to the 3D visual experience, like visual discomfort.…”
Section: Related Workmentioning
confidence: 99%
“…Commonly, in conventional video services the two main possibilities are to discard frames reducing the framerate, or to reduce the video coding quality. Besides, when dealing with 3DTV other approaches could be considered, for example, to switch to a monoscopic version of the transmitted video [15], or to reduce the coding bitrate using asymmetric coding [16]. …”
Section: Analyzed Impairmentsmentioning
confidence: 99%
“…For example, dealing with stereo views, the effects of coding artifacts could be more annoying if each view is affected differently, making the fusion of both images difficult for the HVS. For instance, it has been shown that when blocking effects affect each view differently, binocular rivalry could be produced [2]. Some other studies analyzed the effects of coding V+D formats, showing that the HVS is less sensitive to distortions affecting the depth map than those degrading the quality of video color [34].…”
Section: Effect Of Coding Artifactsmentioning
confidence: 99%
“…One example can be found in [2], where Barkowsky et al carried out a subjective study of the effects of different patterns of packet losses in a simulcast scenario. In addition, various error concealment techniques for 3DTV were analyzed.…”
Section: Effect Of Transmission Errorsmentioning
confidence: 99%
“…In this paper a study of the impact of transmission errors in 3DTV is presented. In contrast to the numerous studies of this type of distortions made for conventional video [5] [6], only a few publications exist for stereoscopic sequences [7] [8]. Moreover, little research has been done analyzing the performance of the first approaches for delivering 3DTV that are being recently used [9].…”
Section: Introductionmentioning
confidence: 99%